Growth Restriction, Osteopenia, Placental Massive Perivillous Fibrin Deposition With (or Without) Intervillous Histiocytes and Renal Tubular Dysgenesis—An Emerging Complex. (January 2018) - Abdulghani, Sahar; Moretti, Felipe; Nikkels, Peter GJ; Khung-Savatovsky, Suonavy; Hurteau-Miller, Julie; Grynspan, David
We describe a case of a pregnancy complicated by early onset asymmetric growth restriction with anhydramnios with termination occurring at 21 weeks. Fetal autopsy showed demineralization of bones and renal tubular dysgenesis. Placental pathology showed features of massive perivillous fibrin deposition and chronic histiocytic intervillositis. We review prior documentation of this association and briefly discuss potential pathogenesis.